Taḥlīl al-Bunūd al-Ikhtibār Fī Mādah al-Muḥādaṡah Bi Ma`had Jāmi`ah ar-Rānīry Dār as-Salām: تحليل بنود الاختبار في مادة المحادثة بمعهد جامعة الرانيري دار السلام - Nanda A`thani; Moch. Fajarul Falah; Mukhlisah Mukhlisah (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2022)
Ma’had Al-Jami’ah Ar-Raniry Darussalam has many students from different departments, including the Department of Biology, Department of Physics, and some others, the researcher noticed that most of them are able to answer questions correctly in the exercises. In fact, that book shows the short material and many tests, and each test has a variety of items. Therefore, the researcher wanted to analyze the form of the test items. In this paper, the researcher determines whether the test items in the Conversation Subject at the Ma’had Al-Jami’ah Ar-Raniry Darussalam are appropriate in terms of the level of validity, reliability, difficulty, and in terms of the level of discrimination. The purpose of scientific writing is to find out the suitability of the test items in the Conversation Subject At The Ma’had Al-Jami’ah Ar-Raniry Darussalam in terms of the level of validity, reliability, difficulty, and in terms of the level of discrimination. As for the research method that the researcher used, it is the content analysis method. The population in this research is all students in SCTV’s dormitory which is 183 students and the research took 22 students for sampling. In data collection researcher used documentation, that is, the test items in the Arabic Language Lessons Book for Non-Native Speakers Part One and the author is Dr. F. Abdurrahim in the Conversation Subject At The Ma’had Al-Jami’ah Ar-Raniry Darussalam. Based on the research can be obtained that the questions test which presented by the teacher are not in accordance with the standard item test in terms of validity, reliability, level of difficulty, and discrimination.